Ekplorasi Etnomatematika Pada Budaya Malam Nujuh Likur Atau Malam Ke 27 Ramadhan Masyarakat Seluma - Anggita Metia Nopikasari; Novi Ayu Ramadhan Harahap; Betti Dian Wahyuni (Yayasan Darussalam Bengkulu, 2023)
This study aims to determine the process or activities of the night of Nujuh Likur in Seluma, the meaning of the night of Nujuh Likur activities for the people of Seluma, and the mathematical elements contained in the night of Nujuh Likur activities. The night of Nujuh Likur activities are usually carried out in the holy month of Ramadan or are often carried out when commemorating the night of Nuzulul Qur'an and the night of Lailatul Qadar, the meaning contained in this activity is seen from a religious perspective, and there are mathematical aspects in the night of seven likur activities. Aspects that exist include arithmetic sequences, the mention of the number twenty by the Serawai community and the concept of Measurement.